ANALYSIS OF NON PERFORMING LOAN AND CAPITAL ADEQUACY RATIO AMONG CHINESE BANKS IN THE POST-REFORM PERIOD IN CHINA - CAI, Mei; HUANG, Zhonglin (Journal of Advanced Studies in Finance; Vol 5 No 2 (2014): JASF Volume V, Issue 2(10), Winter, 2014, 2014)
In this paper, we use the panel data to analyze the correlation among the Return on Assets (ROA), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), and other important factor that influence the internal and external environment such as deposit, total assets, GDP and Interest Rate. Our results indicate that NPL has no effect on ROA and the impact of CAR is negative.